Quantification of metal‐acid balance in hydroisomerization catalysts: A step further toward catalyst design. Issue 7 (26th January 2017) - Mendes, Pedro S. F.; Silva, João M.; Ribeiro, M. Filipa; Duchêne, Pascal; Daudin, Antoine; Bouchy, Christophe
Abstract : A methodology was developed to interpret the results of n‐paraffins hydroisomerization over bifunctional catalysts based on two simple kinetic models used consecutively. First, a macrokinetic model was used to obtain the corresponding turnover frequency over the acid sites and the maximum of C16 isomer yield. Second, a dual‐function model was used to correlate these catalytic descriptors to the ratio of metal to acid sites of the catalyst. To illustrate the methodology, Pt/HBEA and Pt/HUSY catalysts with different Pt loadings were evaluated. The impact of metal‐acid balance on the catalytic turnover frequency and the maximal C16 isomer yield were adequately captured for the bifunctional HUSY and HBEA catalysts. Moreover, the parameters of the dual‐function model revealed to be intrinsic to the catalytic properties of the zeolite under the scope. This methodology is believed to be of interest for information‐driven catalyst design for the hydroisomerization of n‐paraffins. © 2017 American Institute of Chemical Engineers AIChE J, 63: 2864–2875, 2017